Evolution of Mediterranean Sea water properties under climate change scenarios in the Med-CORDEX ensemble - Soto-Navarro, Francisco Javier; Jordà, Gabriel; Amores, Ángel; Cabos, William; Somot, Samuel; Sevault, Florence; Macías, Diego; Djurdjevic, Vladimir; Sannino, Gianmaria; Li, Laurent; Sein, Dimitri (Springer-Verlag, 2020)
Twenty-first century projections for the Mediterranean water properties have been analyzed using the Med-CORDEX ensemble. It is comprised by 25 simulations, 10 historical and 15 scenario projections (11 are ocean–atmosphere coupled runs and 4 are ocean forced runs). The emissions scenarios considered are: RCP8.5, RCP4.5 and RCP2.6. All simulations project a warming across the entire basin by the end of the century as a result of the decrease of heat losses to the atmosphere through the sea surface and an increase in the net heat input through the Strait of Gibraltar. The warming will affect the whole water column with higher anomalies in the upper layer. The change projected by the end of the century ranges between 0.81 and 3.71 °C in the upper layer (0–150 m), between 0.82 and 2.97 °C in the intermediate layer (150–600 m) and between 0.15 and 0.18 °C in the deep layer (600 m—bottom). Its intensity is strongly dependent on the choice of emission scenario and, in second order, on the choice of Global Circulation Model used to force the RCM. Salinity will also increase due to the increase of the freshwater deficit and the related increase in the net salt transport at the Gibraltar Strait. In the upper layer this process can be damped or enhanced depending on the characteristics of the inflowing waters from the Atlantic. This depends on the evolution of salinity in the Northeast Atlantic projected by the GCM. The salinity changes projected for the whole basin range between 0 and 0.34 psu in the upper layer, between 0.08 and 0.37 psu in the intermediate layer and between − 0.05 and 0.33 in the deep layer. These changes in the temperature and salinity modify the characteristics of the main water masses as the new waters become saltier, warmer and less dense along the twenty-first century. As a consequence, the intensity of the deep water formation in the Gulf of Lions is expected to decrease, while no clear results are obtained for Adriatic Sea and in the Aegean Sea.
Se adjunta la versión postprint aceptada, que incluye las correcciones de de los revisores, debido a que la editorial tiene los derechos de copyright y no permite la difusión en acceso abierto de la versión publicada. Puede accederse a la misma a través del DOI que se incluye en los datos de la publicación.
Keywords: Mediterráneo; Mares y océanos - Temperatura; Cambios climáticos; Mediterranean Sea; Regional Climate Models; Climatic projections; Salinity trends; Temperature trends; Med-CORDEX